An eﬀective new one-step block integrator for the numerical solution of system of ﬁrst order diﬀerential equation arising from epidemiology models - Modebei, M.I.; Olaiya, O.O.; Faniyi, O.E.; Anorue, O.F. (International Journal of Mathematical Analysis and Modelling, 2024)
This paper proposes an eﬀective new one-step block integrator for the solution of system of ﬁrst order ordinary diﬀerential equation that arises from models in epidemiology in life science. Showing the performance of this method, SIR, SEIR and more compartmental models are solved numerically and thus comparing with the classical Runge-Kutta to reveal its accuracy. The numerical results obtained clearly shows that the proposed method is more eﬃcient and robust for obtaining the numerical solution of mathematical models in epidemiology.